FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KARYAWAN PADA CV. GRANADA - Subarjo Subarjo (Optimum: Jurnal Ekonomi dan Pembangunan, 2015)
This research is a descriptive study that aims to determine the effect eitherpartially or simultaneously between the level of education, age of work, motivation andwork experience on employee productivity. This research was conducted at CV Granadawhere the overall number of employees 50 people used as a sample in this study. Validityand reliability, Normality Test and Classical Assumption Test carried out on the researchinstrument before the data were tested using multiple linear regression analysis.Multiple Linear Regression Test results showed that partially working age, motivation,and work experience positive and signifi cant impact on employee productivity, while theeducation level is not proven effect. Simultaneously between level of education, age ofwork, motivation and work experience have a signifi cant effect on employee productivity